Simulation Model for Investigation of Probable Activity Production Rates - T, Akash (International Journal of Innovative Research in Computer Science and Technology, 2025)
The construction industry is the key to the infrastructure development around the world; however, it is often faced with uncertainties that interfere with the implementation of projects and cause inefficiencies. The correct estimation of the production rate of the activities, i.e. the amount of output that can be produced in a particular suggested unit time or resources, in cases like excavation, pouring concrete or installing steel is vital to robust project planning, scheduling and cost management. The traditional deterministic methods that presuppose the existence of fixed input such as historical averages or expert opinions, do not usually reflect the dynamic variation of the construction settings. Issues like variable labor productivity, variable supply of materials, weather issues and site constraints add much risk into the equation and result in delays and cost overruns on around 70 percent of projects globally. The paper offers solutions to these problems as it is based on creation of very advanced model that uses simulation method due to estimation of likely rates of production taking probabilistic factor to reflect complexities that exist in the real world. The key aims are to create a Monte Carlo simulation framework that will simulate rates of production under uncertainty and show its accuracy with historical data of a project and to assess the effects on important project cost and time metrics. The model was developed in Python with the help of libraries like NumPy which is used to perform numerical calculations and statistical analysis performed using SciPy. The model uses probability distributions (exemplified by a triangular probability distribution applied to chooses labor productivity and a normal probability distribution applied to weather delays) to simulate thousands of iterations. The results/outputs contain average levels of productions, confidence intervals, risk profile, which gives an overall idea of the results that can be obtained. The utility of the model is demonstrated by a case study of a mid-scale commercial building project which indicates that uncertainty effects can change the rate estimates of production by up to 25 percent in cases where the deterministic models are used. Sensitivity analyses allow pointing out important sources of uncertainty, including factors like labor variation and delayed materials so that risk mitigation activities can be purposefully focused. Findings are an improvement in the predictive accuracy with the mean absolute percentage error being less than 10 percent when compared to historical data as compared to traditional methods. The implications of the model include better resource assignment, intelligent choice, and a 15-20 percent decrease in project risks so that there is efficiency and cost effectiveness. Filling the gaps in probabilistic modeling, the work proposes an efficient user-friendly instrument to practitioners and researchers in the construction domain since it is scalable, consistent with the trend toward digitalization of construction industry in projects with Building Information Modeling (BIM) and documents the nature of the project through data-driven management, which can promote sustainable approaches.